Policy Challenges for Campus Teaching Programs in Non-Educational Study Programs - Ambarwati, Arie; Pramudiana, Ika Devy (Postgraduate Program, State Islamic Institute (IAIN) Kediri, Indonesia, 2023)
The purpose of this research is to find out and describe the challenges faced by non-educational study programs in sending their students to take part in the Kampus Mangajar program as one of the Merdeka Belajar Kampus Merdeka (MBKM) policy programs. This research uses a descriptive approach with qualitative research methods. The data collection techniques used in this research were in-depth interviews, observation, and documentation studies. The selection of informants was carried out using the purposive sampling technique or sampling theory. Research findings show that there are two challenges, namely administrative challenges, and technical challenges. The administrative challenge is that universities must take their policies in implementing MBKM following their financial conditions and capabilities. The challenges faced in implementing the Teaching Campus MBKM program include limited funds, especially from students, and the academic information system to facilitate activities is still inadequate. lack of information regarding the technical implementation of the MBKM program. Among the challenges described, several similar challenges are found in many universities, namely: funding, academic systems, quality, and productivity of human resources. Technical challenges in Kampus Mengajar programs include issues of communication competence in teaching, challenges of literacy skills as well and mental attitude as something fundamental in learning activities.